Peran pemuda dalam mewujudkan demokrasi yang sehat di Indonesia - malikha, hilda himmatul (Maliki Interdisciplinary Journal, 2026)
Youth play a strategic role in supporting the realization of a healthy democracy in Indonesia. As a significant part of the national demographic with broad access to information technology, youth are capable of being agents of change, promoting transparency, participation, and accountability in the democratic system. However, various challenges such as political apathy, limited political education, and the dominance of pragmatism hinder optimal youth involvement. This study aims to examine the role of youth in Indonesian democracy and strategies that can strengthen their contribution. The method used is a qualitative literature review. The results indicate that strengthening political education, digital literacy, and creating inclusive participation spaces are key to empowering youth in realizing a healthy democracy. The use of digital media by youth demonstrates a shift in political participation patterns that are increasingly open and interactive. Social media has become a means to convey aspirations, criticize policies, and build social movements, although it also faces challenges such as disinformation and low digital political literacy. Therefore, synergy between the government, education, and society is needed to support the role of youth as drivers of inclusive and sustainable democracy.